Aggregate Savings, Financial Intermediation, and Interest Rate - Gupta, Kanhaya L. (The Review of Economics and Statistics, 1987)
There has been considerable controversy about the role of financial factors as determinants of savings in developing countries. This paper explores the importance of two such factors, namely, real interest rate and financial intermediation. Using pooled time- series, cross-section data, a model of savings is estimated for Asia, Latin America, and for the total sample. Particular attention is paid to the error structure in estimation. The results suggest that pooling is not justified. Further, there is no unequivocal support for the effect of either of the two factors; some qualified support is found for Asia but none for Latin America. Copyright 1987 by MIT Press.